A supramolecular near-infrared nanophotosensitizer from host-guest complex of lactose-capped pillar[5]arene with aza-BODIPY derivative for tumor eradication. Issue 8 (22nd March 2023) - Li, Jiaxuan; Lv, Xiaomeng; Li, Jiahui; Jin, Wenjuan; Chen, Zelong; Wen, Yafei; Pei, Zhichao; Pei, Yuxin
Abstract : A supramolecular NIR nanophotosensitizer for dual-modal imaging and ablation of tumors was constructed by loading disulfiram (DSF) into the vesicle from host–guest complex of lactose-capped pillar[5]arene (LacP5) with aza-BODIPY derivative (BSTA). Abstract : Aza-BODIPY is a multifunctional near-infrared fluorescent dye, and modifications around the aza-BODIPY core can not only construct various sensors but also generate phototherapeutic agents (PAs) with desirable properties. Constructing aza-BODIPY based phototherapy system has become an intriguing topic in cancer therapy. To overcome the obstacles of phototherapy in clinical application, although some supramolecular phototherapy systems have been reported, it is still highly desirable to construct novel phototherapy supramolecular vesicles for active targeting and dual phototherapy. Here, a novel dual phototherapeutic aza-BODIPY supramolecular vesicle was constructed based on the amphiphilic complex formed by the lactose-capped pillar[5]arene (LacP5) and aza-BODIPY derivative (BSTA). The supramolecular vesicles LacP5⊃BSTA have been demonstrated to have good stability under physiological conditions, active targetability to liver cancer cells, stimuli-responsive drug release, and dual-mode imaging in vivo (fluorescence and photothermal). Supramolecular vesicles loaded with the drug disulfiram (DSF) released aza-BODIPY and DSF in response to glutathione (GSH) in tumor cells, allowing dual phototherapy and chemotherapy. In vivo antitumor experiments reveal that the synergistic therapy based on dual phototherapy and chemotherapy showed enhanced antitumor effects and good biosafety. LacP5⊃BSTA supramolecular phototherapeutic vesicles have great potential in tumor therapy.